UTILIZING KOJIC ACID AND SODIUM ALGINATE AS ANTIBACTERIAL ON CRYOPRESERVED BUFFALO BULL’S SEMEN - Mahdi , Z. A.; Banana , H. J.; Mohammed, O. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This experimental trial was carried out at the Department of Artificial Insemination – Ministry of Agriculture and the laboratories of the College of Agricultural Engineering Sciences/ University of Baghdad from 18 January to 24April 2022. Experiment was conducted to investigate the effect of using sodium alginate and kojic acid in the Tris extender. The goal was to evaluate their effects on the properties of cryopreserved buffalo bull semen and to assess their effectiveness in reducing microbial load. After collecting semen and diluting it with a Tris extender, five experimental groups were designed. T1 )negative control( with no antibiotics, T2 ) positive controlled (with conventional antibiotics )Gentamicin 0.4 IU and Tylosin 0.08/100 IU/ml(, T3 represents a Kojic acid (0.06 g/L), T4 functioned as Sodium alginate at (0.6 mg/mL), and T5 included the combination of Kojic acid (0.06 g/L) and sodium alginate (0.6 mg/ml). The diluted semen was cryopreserved following recommended procedures, where the cryopreserved semen characteristics were assessed, including the plasma membrane integrity of sperm, individual motility, and bacteriological tests; the total number of bacteria in the treated groups score. In addition, the total count of E. coli bacteria and the total count of Staphylococcus spp. After 2 days, 48 hours, 2 and 3 months of cryopreservation for cooled and frozen sperm. The study findings indicate a significant enhancement (P≤0.05)in individual motility and viability for T3, T4, and T5 treatments compared to the T1 and T2 groups. In addition, a significant decreases (P≤0.05) was observed in the overall bacterial count.